Power electronics - Subrahmanyam, Vedam ([S.l.] : *Halsted Press, 1997)
This book provides a comprehensive and a rigorous analytical treatment of static power converters employing mainly thyristors. These power converters include phase controlled line commutated converters, cycloconverters, A.C. voltage controllers, D.C. choppers and inverters. It gives a detailed discussion of the devices which include GTOs and MOSFETs. The analysis in this book is based on circuit approaches and conclusions are aimed at helping in the design of converters. Some important features of the book are: In depth coverage of solid state power converters Extensive comparative analysis of power converters with a view to providing design criteria Numerous worked examples, practice problems and multiple choice questions for an indepth and clear understanding of concepts Application of converters in the speed control of electric motors is discussed in detail. This book would serve as a useful text for undergraduate and graduate courses in Power Electronics and also as a reference for practising engineers who are involved in the design and development of the power electronic converters.